Numerical investigation of the turbulence characteristics and energy dissipation mechanism of baffle drop shafts - Qinghua Yang (IWA Publishing, 2021)
The baffle drop shaft is widely used in deep tunnel drainage systems due to its fine applicability and high energy dissipation. To fully study the turbulence characteristics and energy dissipation mechanism of baffle drop shafts, a 1:25 scale physical model test and a numerical simulation based on the Realizable k-ε model and Volume of Fluid (VOF) method were performed. The results showed that a baffle spacing that is too dense or too sparse is not conducive to energy dissipation and discharge. The minimum baffle spacing is the optimal structural design at the design flow rate when the flow regime is free-drop flow. The energy dissipation calculation model established in this paper has high accuracy for calculating the energy dissipation rate on the baffles in free-drop flow. The energy dissipation modes of the shaft can be divided into inlet energy dissipation, baffle energy dissipation, and shaft-bottom energy dissipation. Baffles play a major role in the energy dissipation at low flow rates, and the proportions of inlet and shaft-bottom energy dissipation increase with the increase in flow rate. HIGHLIGHTS The calculation model of baffle energy dissipation has a better ability to predict the energy dissipation rate of the baffle drop shaft in the free-drop flow regime.; This paper elaborates on the energy dissipation mechanism of the baffle drop shaft through energy dissipation type and energy dissipation mode, which can provide help for in-depth analysis of the energy dissipation characteristics of baffle drop shafts.;